Development Of Google Sites-Based Procedural Text Teaching Materials for Class VII - Jauza, Siti Alya; Lubis, Fitriani (Seloka: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2023)
This study was conducted based on a lack of variation, content, and learning indicators in procedural text teaching materials, so it is necessary to develop teaching materials based on Google Sites that can add variety to teaching materials, contain various types of content in the form of visual, audio, and audiovisual, and also contain all learning indicators. This study describes the stages of development and feasibility of Google Sites-based procedural text teaching materials for class VII. This study used the research and development method of the Borg and Gall model, which was adapted from ten stages to seven stages according to the needs, capabilities, and scope of the study. The results showed that 1) the stages of development of Google Sites-based procedural text teaching materials for class VII began with the potential and problem analysis stage conducted by unstructured interviews with teachers and analyzing the shortcomings of teaching materials used by teachers in learning activities. The next stage is data collection in the form of needs analysis, product design stage, product validation stage by material expert validators, media design, and subject teachers, product revision stage, product trial stage in the form of student responses, and the final product. 2) the feasibility of Google Sites-based procedural text teaching materials has obtained a score from the material expert validator of 88.33%, a score from the media design expert validator of 87.5%, as well as the assessment scores of subject teachers and product trial scores in the form of responses students who each gave a result of 90% and 87.75%. The "very feasible" category is given when the scores obtained from the validator and trials are more than 80%. Based on these results, it can be concluded that Google sites-based procedural text teaching materials for class VII are valid or suitable for use in learning.